Time, space and entrepreneurship - Fiet, James O. (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Identifying opportunities is essential to successful entrepreneurial activity; but good opportunities may be missed if entrepreneurs fail to understand when and where to search for them, or appreciate the significance of timing and place in their search. This book identifies and addresses three problems which face aspiring entrepreneurs. The first is finding a promising idea to exploit; the second is to know when to stop searching, or pursue a more promising search; and the third is to understand how the entrepreneur can locate him or herself in time and space to most economically locate a discovery. As well as developing original theories to solve these problems, this book offers practical solutions, which aspiring entrepreneurs can learn and implement through theory-based activities, giving them an opportunity to practice while gaining an understanding of both why and how these approaches work. Showing how timing becomes more salient than time, and place more important than space, this book combines theoretical and practical guidance which will be of great interest to entrepreneurship researchers, educators, students and aspiring entrepreneurs.
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / New Business Enterprises